2019
DOI: 10.1128/aem.01345-19
|View full text |Cite
|
Sign up to set email alerts
|

Glucanase-Induced Stipe Wall Extension Shows Distinct Differences from Chitinase-Induced Stipe Wall Extension of Coprinopsis cinerea

Abstract: This study reports that a high concentration of the endo-β-1,3-glucanase ENG (200 μg ml−1) induced heat-inactivated stipe wall extension of Coprinopsis cinerea, whereas a high concentration of the extracellular β-glucosidase BGL2 (1,000 μg ml−1) did not; however, in combination, low concentrations of ENG (25 μg ml−1) and BGL2 (260 μg ml−1) induced heat-inactivated stipe cell wall extension. In contrast to the previously reported chitinase-reconstituted stipe wall extension, β-1,3-glucanase-reconstituted heat-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…We previously reported that BGL2 performs different physiological functions in stipe elongation and pilei autolysis of C. cinerea [3,12,14]. In the early stage of fruiting-body development, the physiological role of BGL2 in the elongating stipe is to keep the stipe cellwall plastic and synergize with other glucanohydrolases and chitinases to induce wall extension [12,14]. During this stage, excessive hydrolytic activity of β-glucosidase will destroy the structure of the cell wall and affect the elongation of the stipe [12].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that BGL2 performs different physiological functions in stipe elongation and pilei autolysis of C. cinerea [3,12,14]. In the early stage of fruiting-body development, the physiological role of BGL2 in the elongating stipe is to keep the stipe cellwall plastic and synergize with other glucanohydrolases and chitinases to induce wall extension [12,14]. During this stage, excessive hydrolytic activity of β-glucosidase will destroy the structure of the cell wall and affect the elongation of the stipe [12].…”
Section: Discussionmentioning
confidence: 99%
“…The β-1,3-glucanase induces the stipe wall extension activity in the fungi [ 53 ]. It was also reported that extracts from the brown seaweed Laminaria digitata can induce plant systemic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In Coprinopsis cinerea and Coprinus comatus development-related increases in the activities of glucosidase and glucanases, protease and chitinase have been noted during cap expansion (Iten, 1970;Iten & Matile, 1970;Bush, 1974); so, degradation of the substance of the spent gill tissue is provided for by specific enzyme derepression. Whilst in the stipe, specific chitinases and glucanases act synergistically in cell wall extension of C. cinerea (Kang et al, 2019a;Zhou et al, 2019). In earlier stages, prior to the onset of autodigestion, a number of enzymes are specifically derepressed as tissues of the C. cinerea mushroom cap begin to form (Moore, 2013b).…”
Section: Metabolic Regulation In Relation To Morphogenesismentioning
confidence: 99%